Ionizing Radiation and the Physician - Brown, John R. (1963)
The increasing awareness of the medical profession and the general public of the dangers associated with ionizing radiation necessitates a thorough understanding by the physician of the uses and dangers of this hazard. In addition to their application in the fields of diagnosis and therapeutic radiology, x-rays and radioisotopes are increasingly used in research laboratories and in various industries. The effects of low levels of ionizing radiation are still uncertain and it is possible that there is a “threshold” dose at which cellular damage is evident. With the increased number of atmospheric nuclear tests the concentrations of strontium-90, cesium-137, and the shorter lived isotopes such as iodine-131 in food will increase. The present levels of these isotopes do not merit concern and their early efficient removal will assure continued low fallout levels in our major food supplies.